1998
DOI: 10.1002/j.1939-4640.1998.tb02029.x
|View full text |Cite
|
Sign up to set email alerts
|

SP22: A Novel Fertility Protein From a Highly Conserved Gene Family

JEFFREY E. WELCH,
RANDY R. BARBEE,
NAOMI L. ROBERTS
et al.

Abstract: Three nucleotide sequences encoding SP22, a protein originally identified in detergent extracts of cauda epididymal sperm, were isolated from a rat testis cDNA library. While two of these cDNA sequences differed only in their 5′ untranslated regions, a third cDNA was predicted to contain an additional 13 amino acids of coding sequence. Amino acid sequences obtained following Edman degradation of purified SP22 protein and cDNA sequence data both indicated that SP22 was a member of a highly conserved and widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…SP22 was present in three different patterns in addition to no staining on all spermatozoa samples tested, which is in contrast to previous studies that found only equatorial staining and no staining in caudal epididymal and frozen/thawed spermatozoa of all species tested. 5,27 Additionally, the current study found a very small percentage of staining scattered over the head in the caudal epididymal semen samples obtained prior to insulation. This is likely of minor importance since only a low percentage (0.3% ± 0.2) was observed.…”
Section: Discussionsupporting
confidence: 52%
“…SP22 was present in three different patterns in addition to no staining on all spermatozoa samples tested, which is in contrast to previous studies that found only equatorial staining and no staining in caudal epididymal and frozen/thawed spermatozoa of all species tested. 5,27 Additionally, the current study found a very small percentage of staining scattered over the head in the caudal epididymal semen samples obtained prior to insulation. This is likely of minor importance since only a low percentage (0.3% ± 0.2) was observed.…”
Section: Discussionsupporting
confidence: 52%